2018
DOI: 10.1039/c8ra06357e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical bond parameters, bond energy and the local crystal sites of Eu3+ in Ca5(BO3)3F:1% Eu3+ phosphor

Abstract: The coordination environment mechanism of Ca1 (or Eu1), Ca2 (or Eu2), Ca3 (or Eu3) in Ca5(BO3)3F:1% Eu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It is common knowledge that host compounds are crucial to the luminescence process. Ca 5 (BO 3 ) 3 F (CBOF), as initially reported by Li et al, has been demonstrated to be an ideal host for luminescence because of its excellent chemical stability and extraordinary optical properties …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is common knowledge that host compounds are crucial to the luminescence process. Ca 5 (BO 3 ) 3 F (CBOF), as initially reported by Li et al, has been demonstrated to be an ideal host for luminescence because of its excellent chemical stability and extraordinary optical properties …”
Section: Introductionmentioning
confidence: 99%
“…Ca 5 (BO 3 ) 3 F (CBOF), as initially reported by Li et al, has been demonstrated to be an ideal host for luminescence because of its excellent chemical stability and extraordinary optical properties. 2 While CBOF has been recognized as a candidate material with excellent luminescence properties for some time, there has been limited exploration of its preparation methods, which typically involve high-temperature solid-phase techniques. 2 Ionic liquids are environmentally friendly solvents and reactants that possesses low vapor pressure, good thermal stability, and solubility to organic and inorganic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the 4f–4f transition of Eu 3+ is Laporte forbidden, leading to narrow emission spectra with little tunability. 23 According to the relationship between emission spectra and lattice structures, Eu 3+ can be applied as a spectral probe to investigate the roles of the charge compensation, 24 local structure, 25,26 and thermal effect of Ln 3+ -doped nanomaterials. 27,28 Generally, Eu 3+ ions are doped in the MeF 2 by substituting the Me 2+ ions due to their similar ionic radius.…”
Section: Introductionmentioning
confidence: 99%